(untitled) (Journal SCIENCEVOLUTION, 2025)
The emergence of technologies in the workplace has introduced new demands that impact the mental health and professional development of teachers and administrative staff. In this context, the present study analyzed the main psychosocial factors reported in the scientific literature between 1984 and 2024, with the aim of identifying effective prevention and intervention strategies. Using the PRISMA methodology, 50 publications were identified in academic databases, of which 8 met methodological rigor criteria. The findings reveal six recurring risks: work overload and performance pressure, role ambiguity, lack of institutional recognition, limited decision-making autonomy, and unfavorable organizational conditions. These factors compromise the overall well-being of professionals, manifesting in burnout, chronic demotivation, and psychosomatic disorders. As a response, a tripartite action model is proposed, integrating institutional policies with a psychosocial approach, specialized emotional support services, and training in digital competencies from a humanistic perspective, with the goal of fostering healthier, more sustainable educational and work environments centered on collective well-being.